Proceedings of the 2nd Energy Security and Chemical Engineering Congress - Nasrul Hadi, Johari (Springer Nature Singapore, 2023)
Mechanical engineering is a field that is continuously evolving as a profession to provide sustainable design, products and technologies for society. Mechanical engineering products, in conjunction with technological advances in other sectors, contribute to noise, water and air pollution, and the degradation of land and landscape. The rate of production, both energy and products, is increasing at such a rapid rate that natural regeneration can no longer sustain. Emission control is a fast-growing topic for mechanical engineers and others, encompassing the development of machines and processes that produce fewer pollutants as well as new materials and processes that can decrease or eliminate pollution that has already been generated. And, in an increasingly environmentally conscious world, the concept of sustainability is also intrinsically important to the success or failure of any engineering product or processes. Mechanical engineers thus play a central role in applying a truly modern approach for enabling the global transition to green energy and sustainable prac-tices. To address climate change, researchers are progressively looking into a wide range of novel solutions for energy conversion, engine efficiency, alternative fuels, nature-inspired materials, enhanced manufacturing processes and so on. In this context, this book presents part of the proceedings of the Mechanical and Materials track of the 2nd Energy Security and Chemical Engineering Congress (ESChE 2021) as presented by the academics, researchers and postgraduate students. The book provides insights into different aspects of mechanical processes, nanoma-terials and alternate fuels that set the stage for development of sustainable techno-logical solutions. The content of this book will be useful for students, researchers and professionals working in the areas of mechanical engineering, materials, energy technologies, optimization and allied fields.